The Influence of the Collaborative Learning Model on the Achievement of Class X Students at SMA Angkasa 1 Halim Perdanakusuma Jakarta - Prayuda Utama; Bella Stedyan; Siti Nurhasanah; Yayan Sudrajat (Journal of Instructional Development, Innovation, and Evaluation, 2023)
This research aims to determine the effect of the collaborative learning model on the achievement of class X students at SMA Angkasa 1 Halim Perdanakusuma Jakarta FY 2022/2023. The research design used in this research isTrue-Experimental Design.The sampling technique used is bypurposive sampling namely a sampling technique with certain considerations. So the classes used as samples in this research were class X.1 as the experimental class and class X.2 as the control class. Based on statistical analysis the research results show tcount of 20.59 is greater than ttable of 2.02. So it can be concluded that there is an influence of collaborative learning on the achievement of class X students at SMA Angkasa 1 Halim Perdanakusuma Jakarta.